Deferred Tax Expenses, Deferred Tax Assets and Tax Planning on Earning Management - Mulyati, Yati (International Journal of Psychosocial Rehabilitation, 2020)
Financial statements presented by companies to stakeholders and tax authorities must provide assurance that no earnings management practices are in place. This study aims to prove whether earnings management is affected by deferred tax expenses, deferred tax assets, and tax planning. The data used in this study were sourced from financial statements of the property, real estate, and building construction service companies listed on the Indonesia Stock Exchange during 2015-2018. Purposive sampling is a method used in sample selection so that the selected sample of 40 samples is collected and analyzed using multiple regression analysis. From the observed sampling, the results of the study prove that the deferred tax burden affects earnings management, while the deferred tax assets and tax planning do not affect earnings management